(3GdJcedI aj GdMSGHs - (3CHh efUhQ YHO GdbGOQ Hf WGgQ Hf eMeO, GdHZOGOj,J (B429 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi fXQJ ai GdcJH GdMSGHjI ahLOJgG fhYjf, CMOgeG Ydi MO GdGSJbUGA ai CHhGHg Ohf aUhdg s
(3BNQgG (B:s
(3hEf bGd djS ajg cSQ aNGJec ai jSGQIJe GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B385 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B36 s
(3eUOQ GbJfGA GdCUd (B:s
(3dG dg di (B(2708) s
Keywords: (3GdQjGVjGJs